2011
DOI: 10.1134/s1021443712010086
|View full text |Cite
|
Sign up to set email alerts
|

Partial suppression of gene encoding proline dehydrogenase enhances plant tolerance to various abiotic stresses

Abstract: The role of gene of proline dehydrogenase (PDH) in the maintenance of stress tolerance was investigated using the model transgenic plants of tobacco (Nicotiana tabacum L.) carrying an antisense sup pressor of PDH gene (a fragment of Arabidopsis PDH gene under the control of cauliflower mosaic virus 35S promoter in antisense orientation) and notable for a low activity of PDH and elevated content of proline. The progeny of transgenic plants belonging to the 5th generation (T 5 ) with partially suppressed PDH act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 25 publications
1
8
0
2
Order By: Relevance
“…7). It was similar with data obtained with the antisense construct and dou ble stranded RNA suppressor for tobacco plants [7,10,13]. Since the agrobacterial strain that we used had no effect on the metabolism of proline, significant differences between transgenic plants with dsRNA suppressor of ProDH gene and transformed plants in which T DNA is not integrated indicate partial sup pression of proline dehydrogenase gene of sunflower.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…7). It was similar with data obtained with the antisense construct and dou ble stranded RNA suppressor for tobacco plants [7,10,13]. Since the agrobacterial strain that we used had no effect on the metabolism of proline, significant differences between transgenic plants with dsRNA suppressor of ProDH gene and transformed plants in which T DNA is not integrated indicate partial sup pression of proline dehydrogenase gene of sunflower.…”
Section: Resultssupporting
confidence: 85%
“…Several studies have demonstrated a positive corre lation between Pro content and increased tolerance of transgenic plants [5][6][7][8][9][10]. However, participation of L proline in the process of adaptation and stability of transgenic plants is not always obvious, as demon strated by a comparison of the tolerance and Pro con tent in wild species [3,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ABA-hypersensitive prl1 and brassinosteroiddeficient det2 mutants, enhanced Pro accumulation and P5CS1 induction have been recorded. The prl1 mutation reduces the basal level of PDH expression, whereas the det2 mutation increases the inhibitory effect of ABA over PDH (Abraham et al, 2003;Ibragimova et al, 2012). Application of 50 µM ABA to Arabidopsis wild-type, ABA-deficient aba1-1 mutant, and ABA-insensitive abi1-1 and abi1-2 mutant seedlings triggered the expression of AtP5CS and not AtP5CR.…”
Section: Cross-talk Between Pro and Abamentioning
confidence: 98%
“…(b) Proline contents in transformant leaves. (c) Transgenic plants were characterized by elevated tolerance to drought, cold, and toxic salts of heavy metals (Kochetov et al, 2004;Kolodyazhnaya et al, 2006;Ibragimova et al, 2012).…”
Section: заключениеmentioning
confidence: 99%